Examination of Fattening and Slaughtering Performance of Hungarian Merino, Ile de France F1 and Suffolk F1 Lambs - Póti, Péter; Pajor, Ferenc; László, Edina (Acta Agraria Debreceniensis, 2005)
In our examination, we evaluated Hungarian Merino (ram n=30, ewe n=30), Ile de France F1 (ram n=10, ewe n=10) and Suffolk F1 (ram n=10, ewe n=10) lambs. The best fattening performance was shown by the Ile de France F1 lambs (361 g/day). After the fattening period, Hungarian Merino, Ile de France F1 and Suffolk F1 genotypes lambs were slaughtered with a live weight of 30-34 kg. Carcasses were evaluated for dressing percentage, weight of valuable carcass cuts, percentage of valuable meat, bone to meat ratio, as well as meat conformation and fat cover (S/EUROP grading). The slaughter performance proved to be the best for the Suffolk F1 concerned dressing percentage (51,7%), percentage valuable carcass cuts (81,9%). The best percentage valuable meat presented (79,4%) the Ile de France F1 lambs. The best meat conformation and fat covered were in the Suffolk F1 lambs; Hungarian Merinos showed less favourable results. Presently, the results derived from Hungarian practice that Hungarian Merino lambs are not eligible for fattening to great live body weight (30 kg). Therefore, it is necessary to revise the Hungarian Merino lambs with meat sheep breeds.